REKOMENDASI PENINGKATAN KUALIFIKASI DAN KOMPETENSI PERAWAT RUMAH SAKIT X MOJOKERTO MELALUI PENDEKATAN HUMAN CAPITAL - Ahmad Fadholi (UNUSA Press, 2018)
One important aspect of health development is availability of human resources for health. The nurse's challenges in Indonesia is low quality, such as inadequate levels of education and skills. Asmany as 70.4% of nurses in Hospital X Mojokerto not in accordance with the qualifications required in 2014. This study aims to develop recommendations on improving the qualification and competenceof nurse based on human capital approach. This descriptive study used cross sectional design through secondary data analysis from personnel unit of Hospital X Mojokerto. This study shows that nurse qualifications for certain work units and positions are still unfulfilled. Emergency installations, high care units, treatment units III, and operating room units that require nurses with special competencies. The position of head of the room also has not met the criteria in 6 work units. This research formulates recommendations to improve nurses' competence in X Mojokerto Hospital through improvement of recruitment and selection system, provision of continuing education opportunities and training and career preparation for nurses.